Tracked Changes. Fibre ropes. Polypropylene split film, monofilament and multifilament (PP2) and polypropylene high-tenacity multifilament (PP3). 3-, 4-, 8- and 12-strand ropes. (22nd September 2021) - British Standards Institution,
No abstract available